Evaluation Of Anti-Hypertensive And Vasorelaxant Effects Of Gynura Procumbens Merr. Extracts - Iqbal, Zafar (2020)
The cardiovascular diseases are continually increasing in both developed and developing countries. High blood pressure is a well-known “silent killer” which is the leading cause of cardiovascular complications. The inadequate control of blood pressure can develop different complications such as stroke, myocardial infarction, left ventricular hypertrophy, renal and heart failure. Gynura procumbens (G. procumbens) traditionally used for treatment of hypertension. It was hypothesised that, G. procumbens may have anti-hypertensive, hypotensive and vasorelaxant properties due to some active molecules that would lower blood pressure and vasodilations. The dried G. procumbens leaves were ground into a fine powder. The powdered leaves material was serially extracted with petroleum ether, chloroform, methanol and water by maceration process. Each extract was dried under reduced pressure. Four extracts, petroleum ether (GPPE), chloroform (GPCE), methanol (GPME) and water (GPWE) of G. procumbens were obtained. The effect of each extract was examined on isolated rat aortic ring and anesthetized rat preparations. The aims of the present study were to investigate the anti-hypertensive activity in spontaneously hypertensive rats (SHR), vasorelaxant activity in rat aortic ring preparations and blood pressure lowering activity and mechanism of action in anesthetized normotensive rats of G. procumbens extracts. Daily oral administration of GPWE has more anti-hypertensive effects in SHR compared to other extracts. The intravenous (i.v.) administration of GPWE among the extracts also has more blood pressure lowering effects in anesthetized normotensive rats.